Language ideological debates:The case of Croatia - Bertoša, Mislava (Array, 2012)
In this paper we analyse current language ideological debates taking place in Croatia, focusing on the role of language as a marker of national identity and medium of national homogenization. As theoretical framework we adopt anthropological and sociolinguistic views on language ideologies and Critical Discourse Analysis. Data consist of texts that are collected from Croatian media (newspapers, Internet) about relations between language, nationality and identity including attitudes toward dialects and the standard language. Analysis of language ideological debates is articulated around several key points. We want to examine who are the main social actors participating in language debates, and what main topics can be identified. We aim to explore how are the language issues linked to the concept of national identity, what dominant ideologies can be traced in these debates, what is the nature of language policies, as well as what types of discourses regarding language and national identity issues (academic/scholarly, political, popular, pragmatic etc.) circulate and intersect in the public sphere.